2019
DOI: 10.2139/ssrn.3310618
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Findings and Policy Implications from the Nationwide Schistosomiasis and Intestinal Helminthiasis Survey in Sudan

Abstract: Background: The World Health Assembly endorsed the WHO Neglected Tropical Disease (NTD) Roadmap in 2013, in which NTDs were suggested as tracers of equity in the assessment of progress towards the Sustainable Development Goals. Nationwide surveys were undertaken in all 18 states of Sudan to identify the geographical distribution and to estimate the prevalence and intensity of schistosomiasis and other intestinal helminthiases from December 2016 to March 2017. Methods:We used two-stage random sampling. Each dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 2 publications
0
16
2
Order By: Relevance
“…In contrast, the present study showed very much higher prevalence of S. haematobium compared to that obtained from nationwide survey (5.2%), even though, South Darfur States was the second most endemic area with a prevalence of 13.91% in that survey (9). Moreover, many other nding across the country reported lower ndings when the S. haematobium diagnostic stages were screened particularly among children (11,16,17).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…In contrast, the present study showed very much higher prevalence of S. haematobium compared to that obtained from nationwide survey (5.2%), even though, South Darfur States was the second most endemic area with a prevalence of 13.91% in that survey (9). Moreover, many other nding across the country reported lower ndings when the S. haematobium diagnostic stages were screened particularly among children (11,16,17).…”
Section: Discussioncontrasting
confidence: 87%
“…A recent nationwide survey carried out in all the states estimated that the overall prevalence of S. haematobium was 5.2%. The same survey pointed East and South Darfur States as most severe endemic areas (9). However, there are limited data on the burden of the disease in these areas.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…haematobium infection in the White Nile State (21.4%) in 1996 [11] and the baseline prevalence in Al Jabalain before MDA in 2009 (28.5%) [9]. Although the two localities had different MDA histories, the chemotherapeutic effect of a single praziquantel MDA was good and stable based on the observed reduction rate of prevalence.…”
Section: Discussionmentioning
confidence: 96%
“…Sudan has one of the highest schistosomiasis prevalence rates in the world. About 15% of the total population (~ 5.8 million people) requires treatment, with the majority being children [11,12].…”
Section: Introductionmentioning
confidence: 99%